Microfoundations of Internal and External Absorptive Capacity Routines - Lewin, Arie Y.; Massini, Silvia; Peeters, Carine (Organization Science, 2011)
The 20 years following the introduction of the seminal construct of absorptive capacity (AC) by Cohen and Levinthal (Cohen, W. M., D. A. Levinthal. 1989. Innovation and learning: The two faces of R&D. Econom. J. 99(397) 569–596; Cohen, W. M., D. A. Levinthal. 1990. Absorptive capacity: A new perspective on learning and innovation. Admin. Sci. Quart. 35(1) 128–152) have seen the proliferation of a vast literature citing the AC construct in over 10,000 published papers, chapters, and books, and interpreting it or applying it in many areas of organization science research, including organization theory, strategic management, and economics. However, with very few exceptions, the specific organizational routines and processes that constitute AC capabilities remain a black box. In this paper, we propose a routine-based model of AC as a first step toward the operationalization of the AC construct. Our intent is to direct attention to the importance of balancing internal knowledge creating processes with the identification, acquisition, and assimilation of new knowledge originating in the external environment. We decompose the construct of AC into two components, internal and external AC capabilities, and identify the configuration of metaroutines underlying these two components. These higher-level routines are expressed within organizations by configurations of empirically observable practiced routines that are idiosyncratic and firm specific. Therefore, we conceptualize metaroutines as the foundations of practiced routines. The ability of organizations to discover and implement complementarities between AC routines may explain why some firms are successful early adopters and most firms are imitators. Success as an early adopter of a new management practice or an innovation is expected to depend on the extent to which an organization evolves, adapts, and implements the configuration of its internal and external absorptive capacity routines.